Is There Accounting In Assessing the Accuracy of Credit Loan Collateral? - Dian Puspitaningrum; Elva Nuraina; Elana Era Yusdita (Lembaga Riset dan Pengembangan MAPPI, 2021)
This research aims to analyze the accuracy of credit guarantee assessment in providing working capital credit to rural banks. This study uses a qualitative approach with qualitative descriptive research. Data collection techniques using observation, interviews, and documentation. This study's results indicate that the assessment of credit guarantees at rural credit banks has used documents or notes in every checking of collateral and uses special services for collateral appraisers. However, there is no application of fixed assets depreciation to assess the decline in the value of collateral in the future. This assessment should be done to overcome bad credit before the repayment period is complete.